KETABAHAN PEREMPUAN ARAB DALAM RᾹ’IYAH AL-AMAL KARYA RAUḌAH AL-DAKHĪL (Analisis Psikologi Sastra) - Sangidu, Sangidu (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
This study reveals a number of psychological problems experienced by the characters. Those problems concern with the issue on a woman’s expectation of having a husband who can be a leader as well as a shepherd for her self and her children. It was found in the text of the short story called Rā'iyah al-Amal (Waiting For A Shepherd) by Rauḍah al-Dakhīl. Literary psychology theory is used to reveal the problems. Psychology of literature is a discipline that sees literature as a work containing events psychological life of human beings, played by imaginary or factual figures. Meanwhile, according to Allport, Kretch Crutchfield, dan Heuken said that personality of man and woman is the complex unity and consist of psychological aspects and physical aspects. The psychological aspects cover intelligency, nature, attitude, interest, aspiration, qualm, sadness, ambition, emotion, and etc. The qualm and sadness, which are experienced by a young woman in the story will be revealed in this research. The conclusion is that in the beginning of her marriage, the young woman expects her husband would be a Rā’iy al-Amal that is shepherd for her self and her children. But in reality, her marriage had lasted only in four years. Having children is not yet a reality. Therefore, the young woman tried hard to be the shepherd